2018
DOI: 10.1021/acssuschemeng.8b03156
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic and Antagonistic Interactions during Hydrothermal Liquefaction of Soybean Oil, Soy Protein, Cellulose, Xylose, and Lignin

Abstract: We conducted hydrothermal liquefaction (HTL) of soybean oil, soy protein, microcrystalline cellulose, xylose, and lignin as individual compounds and binary, ternary, quaternary, and quinary mixtures at 350 °C for 30 min. The 34.5 wt % biocrude yield from HTL of the quinary mixture, which mimics the biochemical composition of swine manure, is much higher than the 21.5 wt % yield calculated from the weighted average yields from HTL of the individual components. HTL of binary mixtures of protein and cellulose, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
95
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(107 citation statements)
references
References 39 publications
11
95
1
Order By: Relevance
“…A comparison of Figure 7 as a function of alga batch biochemical composition shows that a high protein content frequently corresponded to a high toluene-insoluble content. This observation is in accordance with the results of Lu et al [12], whereby yields higher in protein than carbohydrate resulted in 3).…”
Section: Biocrude Compositionsupporting
confidence: 93%
“…A comparison of Figure 7 as a function of alga batch biochemical composition shows that a high protein content frequently corresponded to a high toluene-insoluble content. This observation is in accordance with the results of Lu et al [12], whereby yields higher in protein than carbohydrate resulted in 3).…”
Section: Biocrude Compositionsupporting
confidence: 93%
“…It was reported that polyphenols presenting in bio-oil were mainly produced from the degradation of lignin through cleavage reactions or cracking of ether-bonds in the raw feedstock. 27,28 However, lignin compound was difficult to degrade even at relative high temperature (250-350 C) due to its high degree of polymerization and complex branching. 29,30 Clearly, supercritical temperature of 390 C employed in this study effectively improved lignin degradation and produced more phenolics compounds, thus realizing high conversion efficiency and selectivity of lignin to polyphenols.…”
Section: Resultsmentioning
confidence: 99%
“…There is a growing awareness that the problematic challenges of waste management, resource depletion, and the loss of valuable and energy-containing waste can all be solved; more efficient use of biowaste will contribute to sustainable development. Food waste and food residue can be converted to bio-oil [41,63,64,65,66,67], biogas [68,69], or biochar [37] with hydrothermal methods. Alternatively, the desirable components can be harvested using an extraction process [27,31,33,49,70].…”
Section: Introductionmentioning
confidence: 99%